Effect of hydrophobic extension of aryl enaminones and pyrazole-linked compounds combined with sulphonamide, sulfaguanidine, or carboxylic acid functionalities on carbonic anhydrase inhibitory potency and selectivity - Heba Abdelrasheed Allam; Mohamed E. Albakry; Walaa R. Mahmoud; Alessandro Bonardi; Shaimaa A. Moussa; Samy Mohamady; Hatem A. Abdel-Aziz; Claudiu T. Supuran; Hany S. Ibrahim (Taylor & Francis Group, 2023)
Design and synthesis of three novel series of aryl enaminones (3a-f and 5a-c) and pyrazole (4a-c) linked compounds with sulphonamides, sulfaguanidine, or carboxylic acid functionalities were reported as carbonic anhydrase inhibitors (CAIs) using the "tail approach" strategy in their design to achieve the most variable amino acids in the middle/outer rims of the hCAs active site. The synthesised compounds were assessed in vitro for their inhibitory activity against the following human (h) isoforms, hCA I, II, IX, and XII using stopped-flow CO2 hydrase assay. Enaminone sulphonamide derivatives (3a-c) potently inhibited the target tumour-associated isoforms hCA IX and hCA XII (KIs 26.2-63.7 nM) and hence compounds 3a and 3c were further screened for their in vitro cytotoxic activity against MCF-7 and MDA-MB-231 cancer cell lines under normoxic and hypoxic conditions. Derivative 3c showed comparable potency against both MCF-7 and MDA-MB-231 cancer cell lines under both normoxic ((IC50 = 4.918 and 12.27 µM, respectively) and hypoxic (IC50 = 1.689 and 5.898 µM, respectively) conditions compared to the reference drug doxorubicin under normoxic (IC50 = 3.386 and 4.269 µM, respectively) and hypoxic conditions (IC50 = 1.368 and 2.62 µM, respectively). Cell cycle analysis and Annexin V-FITC and propidium iodide double staining methods were performed to reinforce the assumption that 3c may act as a cytotoxic agent through the induction of apoptosis in MCF-7 cancer cells.